Remediation of Allophonic Perception and Visual Attention Span in Developmental Dyslexia: A Joint Assay - Zoubrinetzky, Rachel; Collet, Gregory; Nguyen-Morel, Marie-Ange; Valdois, Sylviane; Serniclaes, Willy (Frontiers in Psychology, 2019)
Categorical perception of phonemes and visual-attention span are cognitive processes that contribute independently to poor reading skills in developmental dyslexia. We here explored whether training programs specifically targeting one or the other process do improve reading performance in dyslexic children. The dyslexic participants were trained using either the RapDys program designed to improve phonemic perception or the MAEVA program targeting visual attention span. Each participant was provided the two programs successively for intensive training. Results show specific effects of RapDys on phonemic discrimination, phonemic awareness and pseudoword reading. MAEVA specifically improved visual attention span and irregular word reading. Both training programs contributed to improve regular word reading. The overall findings suggest that both categorical perception and visual attention span remediation contribute to reading.